The Effects of Media Capabilities on the Rationalization of Online Consumer Fraud - Harrison, Andrew (2018)
This research develops and tests a model of online consumer fraud to determine how the capabilities of communication technologies affect the rationalization of fraudulent behaviors. The model is based on research about the rationalization of fraud, media capabilities, and computer-mediated deception. This investigation empirically tests this model by analyzing 459 Facebook advertisements and 1,896 surveys completed by university students. The findings indicate that the capabilities provided by communication technologies affect the extent to which media mask cues of deceit and dehumanize others. As a result, some media capabilities increase one’s willingness to engage in fraudulent behaviors while other capabilities deter those actions. Media capabilities that mask cues of deceit and reduce social presence increase the inclination of individuals to rationalize fraudulent activities, while media capabilities that expose cues of deceit and increase social presence deter individuals from rationalizing acts of fraud. Media offering greater capabilities for reprocessability and transmission velocity decrease the inclination to rationalize fraud, whereas greater capabilities for anonymity, rehearsability, and parallelism increase the inclination to rationalize fraud. In contrast, symbol set variety does not appear to significantly affect the inclination to rationalize fraud